ANALISIS DAMPAK SOSIAL EKONOMI TERHADAP KEJADIAN STUNTING PADA BALITA - Arya, Mahatama; Aromatica, Desna; laelawati, leni (Administratie: Jurnal Administrasi Publik, 2025)
Stunting can affect a child's development and growth in the long term. This research aims to study various factors, including social and economic, which play a role in the incidence of stunting in toddlers. Which will be reviewed specifically from the perspective of family income, maternal education, parental employment, and access to health services. This research's secondary data comes from the National Health Survey, which includes data on health and socio-economics in Indonesia. Analysis was carried out using logistic regression to determine whether there was a correlation between socio-economics and cases of stunting in toddlers. The research results reveal that socio-economic conditions such as family income, maternal education, and access to health facilities influence cases of toddler stunting. For this reason, it is important for socio-economic based interventions to reduce the stunting rate in Indonesia. Policies that support increasing the income of poor families such as providing direct cash assistance and improving the quality of employment opportunities, access to affordable health services with a focus on routine check-ups and immunizations in low-income areas, and maternal education need to be improved through education about nutrition and good child care through posyandu , health centers, and social media. Apart from that, community empowerment to increase local food security can be a solution in providing nutritious food. Collaboration between the government, private sector and NGOs is very important to create policies that support comprehensive stunting prevention.